Prevalence and Prognostic Association of Circulating Troponin in the Acute Respiratory Distress Syndrome. Issue 10 (October 2017) - Metkus, Thomas S.; Guallar, Eliseo; Sokoll, Lori; Morrow, David; Tomaselli, Gordon; Brower, Roy; Schulman, Steven; Korley, Frederick K.
Abstract : Objective: Circulating cardiac troponin has been associated with adverse prognosis in the acute respiratory distress syndrome in small and single-center studies; however, comprehensive studies of myocardial injury in acute respiratory distress syndrome using modern high-sensitivity troponin assays, which can detect troponin at much lower circulating concentrations, have not been performed. Design: We performed a prospective cohort study. Setting: We included patients enrolled in previously completed trials of acute respiratory distress syndrome. Patients: One thousand fifty-seven acute respiratory distress syndrome patients were included. Interventions: To determine the association of circulating high-sensitivity troponin I (Abbott ARCHITECT), with acute respiratory distress syndrome outcomes, we measured high-sensitivity troponin I within 24 hours of intubation. The primary outcome was 60-day mortality. Measurements and Main Results: Detectable high-sensitivity troponin I was present in 94% of patients; 38% of patients had detectable levels below the 99th percentile of a healthy reference population (26 ng/L), whereas 56% of patients had levels above the 99th percentile cut point. After multivariable adjustment, age, cause of acute respiratory distress syndrome, temperature, heart rate, vasopressor use, Sequential Organ Failure Assessment score, creatinine, and PCO2 were associated with higher high-sensitivity troponin I concentration. After adjustment for age, sex, and randomized trial assignment, the hazard ratio for 60-day mortality comparing the fifth to the first quintiles of high-sensitivity troponin I was 1.61 (95% CI, 1.11–2.32; p trend = 0.003). Adjusting for Sequential Organ Failure Assessment score suggested that this association was not independent of disease severity (hazard ratio, 0.95; 95% CI, 0.64–1.39; p = 0.93). Conclusions: Circulating troponin is detectable in over 90% of patients with acute respiratory distress syndrome and is associated with degree of critical illness. The magnitude of myocardial injury correlated with mortality. Abstract : Supplemental Digital Content is available in the text.